2015
DOI: 10.1111/jomf.12217
|View full text |Cite
|
Sign up to set email alerts
|

Vetting and Letting: Cohabiting Stepfamily Formation Processes in Low‐Income Black Families

Abstract: The authors examined cohabiting union formation processes by analyzing in-depth interview data collected from 30 individuals in cohabiting relationships: 15 low-income Black mothers of adolescents and their partners. Prior research suggests that cohabiting union formation is a gradual, nondeliberative process. In contrast, most couples in this study described a gradual but highly deliberative process. Mothers focused primarily on vetting their partners to ensure child well-being and less on when and how their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Problems of interpretation are further compounded when cohabiting partners do not share similar aspirations for marriage or when partners bring unequal resources or power to the relationship (Sassler & Joyner, ; Sassler & Miller, , ). Understanding changes in marital intentions is also complicated by new variation in living arrangements by social class, gender, family background, and children (Rackin & Gibson‐Davis, ; Reid & Golub, ).…”
Section: Research Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…Problems of interpretation are further compounded when cohabiting partners do not share similar aspirations for marriage or when partners bring unequal resources or power to the relationship (Sassler & Joyner, ; Sassler & Miller, , ). Understanding changes in marital intentions is also complicated by new variation in living arrangements by social class, gender, family background, and children (Rackin & Gibson‐Davis, ; Reid & Golub, ).…”
Section: Research Themesmentioning
confidence: 99%
“…Many individuals entering (or reentering) the partner market are also parents (Qian & Lichter, ), both nonresidential and custodial. Parental status may differentially shape union formation for men and women—its timing (Reid & Golub, ), type (cohabitation vs. marriage) or stability (Lichter et al, ; Tach & Halpern‐Meekin, ). Little research has examined whether children exert similar influences on men's repartnering as they do for mother's—despite the growing prevalence of men whose children spend substantial amounts of time in the paternal residence (Meyer, Cancian, & Cook, ).…”
Section: Research Themesmentioning
confidence: 99%
“…Housing security and family relationships are inextricably linked. Research on family formation for lower income families is contextualized by significant economic instability (Edin & Kefalas, 2005; M. Reid & Golub, 2015), with implications for housing.…”
Section: Housing Security and Family Lifementioning
confidence: 99%
“…When people form close relationships, they develop strategies to guide their selections of partners. For instance, research has found that low-income black women pursuing cohabitating unions engage in a process of “vetting and letting” to ensure the well-being of their children (Reid and Golub 2015). Although this vetting of male partners is child focused, mothers are able to assess how certain partners will be as parents and can apply lessons learned from previous relationships.…”
Section: Racial Attitudes Attractiveness and Vetting Strategiesmentioning
confidence: 99%